INTEGRATED REPORTING IN SMEs - Mitrovic, Ranka; Jurcic, Ana; Trifunovic, Dragana (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
Globalization, growth in the volume of transactions in the form of foreign direct investments, an increase of transactions of multinational companies, have led to changes both in the way of doing business and in the way of business reporting. Irregularities in the operations of many companies have led to the need for implementation of the Corporate Management Code. Finally, the need of companies to be social and socially responsible towards the wider social community, but also to the use of resources, has led to the implementation of the Report on sustainable operations. In this connection, the traditional financial statements cannot meet the new requirements, so it is necessary to have a comprehensive joint report that would satisfy the needs of all stakeholders: employees, owners, managers, suppliers, customers, the government and all others. The aim of this dissertation is reflected in pointing out the importance of integrated reporting and the possibility of applying the same in SMEs.